Respuestas

¡La mejor respuesta!
2012-08-14T17:37:14+02:00

m= 2/3                  Y - y = m * (X-x)

x= -2                     Y- (-5)= 2/3 * (X - (-2)

y= -5                     Y + 5 = 2/3 * (X +2)

                            3* (y +5) = 2*(X + 2)

                            3Y + 15 = 2X +4

                            2X - 3Y -11 = 0

                

m= 3/4                Y - y = m * (X -x)

x= 5                    Y -6 = 3/4 (X - 5)

y= 6                  4 * ( Y-6) = 3* (X -5)

                         4Y -24 = 3X -15

                        3X - 4Y +9 = 0